Neonatal bronchopulmonary dysplasia predicts abnormal pulmonary HRCT scans in long-term survivors of extreme preterm birth. Issue 5 (21st January 2009) - Aukland, S M; Rosendahl, K; Owens, C M; Fosse, K R; Eide, G E; Halvorsen, T
Abstract : Background: There is an increasing understanding that extreme preterm birth carries a risk of long-term pulmonary sequelae. A study was undertaken to investigate if, and in what way, neonatal factors were associated with subsequent abnormalities on pulmonary high-resolution CT (HRCT) scanning and if pulmonary function was related to these abnormalities. Methods: HRCT scanning and pulmonary function tests were performed less than 2 weeks apart in 74/86 eligible subjects (86%) born at a gestational age of ⩽28 weeks or with a birth weight of ⩽1000 g within a defined area in Western Norway in 1982–5 (n = 42) or 1991–2 (n = 32). Mean age at examination was 18 and 10 years, respectively. HRCT scans were interpreted by a paediatric radiologist blinded to the clinical data using a structured system allowing scores from 0 to 50. Results: Lung parenchymal abnormalities were found in 64 subjects (86%), the median (interquartile range) score being 3.0 (1.75–5.0) points. Prolonged neonatal requirement for oxygen treatment predicted poor outcome, and an increase of 100 days increased the average HRCT score by 3.8 points (p<0.001). There was also a positive association of the severity of pulmonary function abnormalities with the extent of HRCT abnormalities, exemplified by the relation between forced expiratory volume in 1 s and total HRCT score (β = −0.090; p<0.001). Conclusions: In area-based cohorts of long-term survivors of extremely preterm birth, prolonged neonatal requirements for oxygen treatment predicted subsequent structural abnormalities on HRCT scans and in pulmonary function, and these two outcome measures were interrelated.